The Effect of a Magnetic Field on Solid–Liquid Contact Electrification for Streaming Flow Energy Harvesting - Thanh Ha Nguyen; Kyoung Kwan Ahn (Energies, 2023)
In recent years, the triboelectric nanogenerator (TENG) has been recognized as a promising method for energy harvesting and self-powered devices. However, in order to improve the output efficiency of the TENG, it is necessary to change the types of dielectric materials, which requires advanced technology and a high cost to implement. To address this issue, we developed a parallel electrode magnetic-TENG (Mag-TENG) based on contact electrification of a liquid–solid interface under the effect of the magnetic field, which enhances the output performance of the TENG without having to develop the dielectric material. Our experimental results achieved a higher output of the TENG under the influence of a magnetic field when an increase of the magnetic field strength went from 0 to 360 mT, and the flow rate of unsteady seawater was variable from 390 to 690 mL/min. Specifically, compared to the without-magnetic field case, the output current increased by approximately 6.5 times and the output voltage by 2.7 times. These findings suggested that using a magnetic field to enhance the TENG’s efficiency has significant potential for energy harvesting from seawater and self-powered flow sensors.